Self-assembled low-crystallization nano flower-shaped polyoxometallate catalyst as well as preparation method and application thereof
By self-assembly low-crystalline nanoflower-like polyoxylate catalyst FinkeCo-FeCoNi/S, the problems of high cost and poor stability of Ru-based and Pt-based catalysts are solved, and efficient full water-removal reaction is achieved, and electrocatalytic activity is improved. and stability, suitable for efficient and environmentally friendly renewable energy applications.
Patent Information
- Application Number
- CN202411817516.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Due to the high cost, poor stability and scarcity of resources, existing Ru-based and Pt-based catalysts have high activation energy barriers in the oxygen evolution reaction and hydrogen evolution reaction in the full water dissolution reaction, which affects the energy conversion efficiency and is difficult to meet the efficient and environmentally friendly functions. Renewable energy demand.
The self-assembled low-crystalline nanoflower-like polyoxylate catalyst FinkeCo-FeCoNi/S is used to increase the defect site and reaction contact area of the catalyst through the unique structure and vulcanization treatment of the polyoxylate, thereby enhancing electron transfer capacity and electricity. Catalytic activity.
The overpotential is significantly reduced in the oxygen evolution and hydrogen evolution reaction, the electrocatalytic activity and stability are improved, and the efficient full water removal performance is achieved. The preparation process is simple and environmentally friendly, and it is suitable for large-scale industrial production.
Smart Images

Figure CN119287444A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of energy materials, and in particular to a self-assembled low-crystallization nano-flower-shaped polyoxometalate catalyst and a preparation method and application thereof. Background Art
[0002] In recent years, the widespread use of fossil fuels such as coal, oil, and natural gas has promoted the rapid development of human economy and society, but their excessive burning has caused energy crisis, environmental degradation, and CO 2 The large-scale emission of carbon dioxide seriously threatens the living environment of human beings and the green and sustainable development of society. With the gradual depletion of non-renewable energy, it will be difficult to meet the energy demand in the future, which prompts us to explore efficient and environmentally friendly renewable energy and energy conversion technologies to replace traditional fossil fuels. As one of the core technologies for clean energy hydrogen production, the overall water splitting technology (including hydrogen evolution reaction and oxygen evolution reaction) has broad application prospects. However, the two core reactions of overall water splitting, oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), have a high activation energy barrier, resulting in slow reaction process and high overpotential, which affects the energy conversion efficiency. Commonly used Ru-based and Pt-based catalysts face severe challenges due to their high cost, poor stability and resource scarcity. Therefore, it is particularly important to develop electrocatalysts with excellent performance to improve the efficiency of overall water splitting.
[0003] Polyoxometalates, referred to as polyoxometalates (POMs), are a class of nanometallic oxygen cluster compounds with clear structures and adjustable compositions. Among them, the Finke-type heteropoly compound has a structure similar to a "sandwich", which is mainly composed of two vacant heteropoly anions and metal ions. It has been widely studied in many fields such as magnetism and catalysis. It is composed of two tri-vacant derivatives of Keggin-type or Dawson-type polyanions and a tetranuclear transition metal cluster. Due to its adjustable transition metal center and rich negative charge, it can be used as a potential electron-donating unit. Due to the vacancy, it has more active sites, and the introduction of the transition metal center makes it exhibit high catalytic activity. In addition, the interaction between polyoxometalates and metal clusters in the central energy band can also produce physical and chemical coordination effects.
[0004] Polyoxometalates have stable thermal and redox properties and can be used as electron acceptors, making them ideal "electron sponges". Polyoxometalates have excellent electrochemical properties, simple preparation methods, low costs, and are easy to mass-produce industrially, so they are widely used in the field of electrochemical energy conversion and storage technology. Therefore, how to use polyoxometalates to prepare catalytic materials suitable for efficient water splitting is still an important research topic. Summary of the invention
[0005] The purpose of the present invention is to provide a catalytic material suitable for efficient water splitting that is simple to prepare, green and environmentally friendly, low-cost and easy to operate. A self-assembled low-crystalline nanoflower-like polyoxometalate catalyst, FinkeCo-FeCoNi / S, was synthesized for the first time. The nanoflower-like structure of the catalyst exhibits more defect sites, thereby increasing the contact area of the reaction. This structural characteristic helps to enhance the reaction activity and catalytic efficiency.
[0006] To achieve the above object, on the one hand, the present invention provides a method for preparing a self-assembled low-crystalline nano-flower-shaped polyoxometalate catalyst, comprising the following steps:
[0007] S1. Dissolve cobalt nitrate hexahydrate in deionized water and add Na 8 [HPW 9 O 34 ] After heating until the solution is homogeneous, a precipitate is generated, which is filtered, dried, and then dissolved in water for recrystallization to obtain a sandwich-type polyoxometalate Finke Co;
[0008] S2. Dissolve cobalt nitrate hexahydrate in a mixed solution of deionized water and ethanol, and add ferric nitrate nonahydrate, urea (CH 4 N 2 O) and the sandwich polyoxometalate Finke Co of step S1 are mixed to prepare a precursor solution; the nickel foam is first immersed in the precursor solution for hydrothermal reaction, and then the nickel foam is taken out and immersed in a methanol solution dispersed with ZIF-67 (Co) for reaction, and finally washed and dried to obtain a nickel foam Finke Co-FeCoNi with uniform growth of Finke-type Co-Fe MOF;
[0009] S3, dissolving sodium sulfide nonahydrate in deionized water, and adding the nickel foam of Finke-type Co-Fe MOF in step S2 to carry out a sulfidation reaction, washing and drying after the reaction, and finally obtaining the sulfided nickel foam of Finke-type Co-Fe MOF, that is, the nanoflower-shaped polyoxometalate catalyst Finke Co-FeCoNi / S.
[0010] As a further preferred technical solution of the present invention, in step S1, Na 8 [HPW 9 O 34 ] was prepared by the following method: Na 2 WO 4 Dissolve in water and add H 3 PO 4 Stir with glacial acetic acid to react, and filter to obtain a white crystal precipitate, which is Na 8 [HPW 9 O 34 ].
[0011] As a further preferred technical solution of the present invention, in step S2, the molar ratio of cobalt nitrate hexahydrate to ferric nitrate nonahydrate is 0.5:1.
[0012] As a further preferred technical solution of the present invention, in step S2, the hydrothermal reaction temperature is 100~120 °C.
[0013] As a further preferred technical solution of the present invention, in step S2, cobalt nitrate hexahydrate and 2-methylimidazole are dissolved in methanol to react to obtain ZIF-67 (Co).
[0014] As a further preferred technical solution of the present invention, in step S3, the molar ratio of sodium sulfide nonahydrate to the nickel foam of the Finke-type Co-Fe MOF in step S2 is 2:1.
[0015] As a further preferred technical solution of the present invention, in step S3, the reaction temperature is 100~120 °C.
[0016] According to another aspect of the present invention, the present invention also provides a polyoxometalate catalyst, which is prepared by the above method.
[0017] According to another aspect of the present invention, the present invention also provides an application of a polyoxometalate catalyst in an OER / HER reaction.
[0018] According to another aspect of the present invention, the present invention also provides an application of a polyoxometalate catalyst in the overall water splitting.
[0019] Compared with the prior art, the present invention can achieve the following beneficial effects:
[0020] 1) The catalyst Finke Co-FeCoNi / S synthesized by the present invention uses polyoxometalate Finke Co as a modifier to modify the FeCoNi-based catalyst to achieve the synthesis of low-crystalline nano-flower-shaped catalysts. First, the unique electron storage and release ability of polyoxometalates is cleverly utilized to make Finke Co-FeCoNi / S rich in a large number of vacancy defects, enhance the electron transfer ability, and facilitate the electrocatalytic process. Its nano-flower-shaped morphology exposes more defect sites, thereby increasing the reaction contact area; secondly, sulfiding the catalyst helps to provide an S source during the synthesis of the catalyst, so that more uncoordinated S vacancies are formed on the surface; finally, the introduction of polyoxometalates makes it present a weak crystalline structure, that is, the addition of Finke Co reduces the crystallinity of the catalyst. Compared with high-crystalline materials, low-crystalline catalysts can not only provide a large number of coordinated unsaturated sites, which are helpful for the adsorption of products, but also improve the conductivity of active substances, accelerate the migration rate of electrons, and enhance electrocatalytic activity.
[0021] 2) The catalyst Finke Co-FeCoNi / S synthesized in the present invention undergoes oxygen evolution reaction in 1.0 M KOH alkaline solution with an overpotential of 10 mA·cm -2 Under the condition of only 228 mV, 100 mA·cm -2 Compared with the case without adding polyoxometalate catalyst, Finke Co-FeCoNi / S has faster charge transfer rate, higher electrocatalytic active surface area and stable electrochemical durability. -2 The overpotential is only 75 mV, and the catalytic performance of hydrogen evolution reaction is better than most non-precious metal catalysts reported so far.
[0022] 3) The catalyst Finke Co-FeCoNi / S synthesized in the present invention has excellent overall water splitting performance. Compared with commercial catalysts, it has a current density of 10 mA·cm -2 When the battery is fully decomposed into water, the voltage is 1.52 V.
[0023] 4) The catalyst Finke Co-FeCoNi / S of the present invention not only has a simple preparation process, but also has the characteristics of no three wastes, environmental friendliness, and novel structure. It provides a practical strategy for the development of high-performance, low-cost comprehensive water splitting materials, oxygen evolution reaction and hydrogen evolution reaction, and provides ideas for the design of efficient green energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0025] Figure 1 (ac) scanning electron microscope images, (df) transmission electron microscope images and high-resolution transmission images, (g) electron diffraction SAED images, and (h) elemental surface scan images of the self-assembled low-crystalline nanoflower-shaped polyoxometalate-based catalyst Finke Co-FeCoNi / S synthesized in Example 1.
[0026] Figure 2 (ac) scanning electron microscope images, (df) transmission electron microscope images and high-resolution transmission images, and (g) electron diffraction SAED images of the catalyst FeCoNi / S in Comparative Example 1.
[0027] Figure 3 The infrared spectra of (a) Finke Co-FeCoNi / S and Finke Co catalysts in Example 1, and (b) XRD patterns of Finke Co-FeCoNi / S, Finke Co and FeCoNi / S in Comparative Example 1.
[0028] Figure 4 Finke Co-FeCoNi / S catalyst and commercial RuO 2 / Ni, FeCoNi / S catalyst in comparative example 1, and nickel foam (a) LSV polarization curves of oxygen evolution test in 1.0 M KOH solution; (b) at 10 mA / cm -2 and 100mA / cm -2 Overpotential comparison under current density; (c) Tafel slope of the catalyst; (d) Stability test diagram of Finke Co-FeCoNi / S and FeCoNi / S in Comparative Example 1 after 1000 cycles; (e) LSV polarization curve of hydrogen evolution test; (f) LSV polarization curve of complete water splitting.
[0029] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0030] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0031] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0032] The commercial Pt / C (20%) and RuO 2 The catalyst and nickel foam were purchased from Sigma-Aldrich.
[0033] Example 1
[0034] This embodiment provides a method for preparing a self-assembled low-crystalline nano-flower-shaped polyoxometalate catalyst, and the specific steps are as follows:
[0035] Step 1, preparation of Finke Co:
[0036] Put 12 g Na 2 WO 4 Dissolve in 15 ml of water, then add 0.3 ml of H 3 PO 4 After vigorous stirring with 2.2 ml of glacial acetic acid, the white crystal precipitate was Na 8 [HPW 9 O 34 ]; will Co(NO 3 ) 26H 2 Dissolve 20 ml of O in water and add 2.414 g of Na 8 [HPW 9 O 34 ]After heating until the solution is homogeneous, a precipitate is generated, which is filtered and dried, and then dissolved in hot water and recrystallized to obtain a sandwich polyoxometalate Finke Co, referred to as Finke Co.
[0037] Step 2: Preparation of Finke Co-FeCoNi:
[0038] First, weigh 0.38 g Co(NO 3 ) 2 6H 2 O was dissolved in a mixed solution of 20 mL deionized water and 10 mL ethanol, and 1.07 g Fe(NO 3 ) 3 9H 2 O, 0.48 g CH 4 N 2 O and 400 mg Finke Co were stirred and mixed evenly, then transferred to a polytetrafluoroethylene autoclave, and a piece of nickel foam (NF) was placed in it. The heating was continued for 6 h at a reaction temperature of 120 ° C. After the autoclave was naturally cooled to room temperature, the NF after the reaction was rinsed with deionized water and placed in a vacuum drying oven at 80 ° C for use;
[0039] Add 0.58 g Co(NO 3 ) 2 6H 2 O was dissolved in 25 mL of methanol and magnetically stirred at room temperature for 30 min to obtain solution A; 1.6 g of 2-methylimidazole was dissolved in 25 mL of methanol and stirred by ultrasonication to obtain solution B; solutions A and B were mixed and stirred for 1 h to generate a methanol solution of Co-containing zeolite imidazolate framework ZIF-67 (Co);
[0040] The dried NF was immersed in a methanol solution of ZIF-67 (Co) and allowed to stand for 24 h. After washing with water, it was dried in vacuum at 80 °C to obtain a nickel foam Finke Co-FeCoNi with uniform growth of Finke-type Co-Fe MOF.
[0041] Step 3: Preparation of Finke Co-FeCoNi / S:
[0042] Sodium sulfide nonahydrate was dissolved in 20 mL of deionized water and then transferred to a polytetrafluoroethylene autoclave, and the prepared Finke Co-FeCoNi was placed in it and reacted at 120 °C for 2 h. After the reaction, it was rinsed with deionized water and finally dried in vacuum at 80 °C to obtain the sulfided Finke-type Co-Fe MOF nickel foam catalyst Finke Co-FeCoNi / S, referred to as FFCNS ( Figure 1 ).
[0043] Comparative Example 1
[0044] As a control experiment of Example 1, the difference from Example 1 is that Finke Co was not used in preparing the catalyst. The specific steps are as follows:
[0045] Step 1, preparation of FeCoNi:
[0046] First, weigh 0.38 g Co(NO 3 ) 2 6H 2 O was dissolved in 20 mL of deionized water and 10 mL of ethanol, and 1.07 g of Fe(NO 3 ) 3 9H 2 O, 0.48 g CH 4 N 2 O, stir and mix evenly at room temperature, transfer the solution to a polytetrafluoroethylene autoclave, put in a piece of nickel foam (NF), and perform hydrothermal reaction at 120 °C for 6 h; wait for the autoclave to cool naturally to room temperature, rinse the nickel foam after the reaction with deionized water for several times, and place it in a vacuum drying oven at 80 °C to dry for later use.
[0047] Add 0.58 g Co(NO 3 ) 2 6H 2 O was dissolved in 25 mL of methanol and magnetically stirred at room temperature for 30 min to obtain solution A; 1.6 g of 2-methylimidazole was dissolved in 25 mL of methanol and stirred by ultrasonication to obtain solution B; solutions A and B were mixed and stirred for 1 h to obtain a methanol solution of ZIF-67 (Co);
[0048] The dried NF was immersed in a methanol solution of ZIF-67 (Co) for 24 h, washed with water and dried in vacuum at 80 °C to obtain nickel foam FeCoNi of Co-Fe MOF.
[0049] Step 2, preparation of FeCoNi / S:
[0050] Sodium sulfide nonahydrate was dissolved in 20 mL of deionized water, and then the solution was transferred to a polytetrafluoroethylene autoclave, and the prepared FeCoNi was placed in it for hydrothermal reaction at 120 °C for 2 h. After the reaction, the nickel foam was taken out, rinsed with deionized water continuously, and finally vacuum dried at 80 °C to obtain the sulfided Co-Fe MOF nickel foam catalyst FeCoNi / S, referred to as FCNS ( Figure 2 ).
[0051] The morphology and microstructure of the catalysts prepared in Example 1 and Comparative Example 1 were analyzed:
[0052] For the Finke Co-doped Finke Co-FeCoNi / S catalyst, scanning electron microscopy (SEM) images showed that the FFCNS exhibited a nanoflower-like structure formed by self-assembly of closely connected nanosheets ( Figure 1 ac), similar to hydrangea; from the high-resolution transmission image, it can be observed that thin-sheet nanoflowers are generated and no obvious lattice fringes are observed. The SAED spectrum shows weak crystallinity ( Figure 1 dg); The element distribution diagram shows that the elements in the catalyst are evenly distributed ( Figure 1 h). In contrast, the FeCoNi / S catalyst without Finke Co doping exhibits an irregular morphology of closely cross-stacked nanosheets ( Figure 2 ac), the high-resolution transmission image shows obvious lattice fringes ( Figure 2 dg), indicating that the catalyst has good crystallinity. By comparison, it can be seen that the introduction of polyoxometalate Finke Co promotes self-assembly, forming a more regular nanoflower-like structure with reduced crystallinity. The nanoflower-like structure can significantly improve the catalytic performance due to its unique three-dimensional structure and highly exposed active sites: first, the nanoflower-like structure is composed of thin sheets and has a large specific surface area, so that more active sites are exposed, increasing the contact area between the reactant and the catalyst, thereby improving the catalytic activity; secondly, this three-dimensional structure constructs a good conductive network, accelerates charge transfer, reduces reaction impedance, and further improves catalytic efficiency. In addition, the microscopic pores and interwoven nanosheets in the flower-like morphology provide a convenient transmission path for electrons, which helps to enhance the catalytic performance in electrochemical reactions. The layered self-supporting structure of nanoflowers enhances its stability under reaction conditions, reduces the risk of catalyst agglomeration and deactivation, and prolongs its service life. Therefore, the present invention reduces the crystallinity of the Finke Co-FeCoNi / S catalyst due to the introduction of Finke Co, resulting in it having abundant defects, which serve as active sites to enhance the interaction between the catalyst and the reactant, thereby improving the catalytic activity. At the same time, the paths for electron and ion transmission in weakly crystalline materials are freer and the migration barriers are lower, thereby increasing the speed of electrochemical reactions.
[0053] Infrared comparison of Finke Co-FeCoNi / S and Finke Co ( Figure 3 a) The prepared FFCNS sample retains the characteristic peaks of Finke Co, as shown by the XRD pattern ( Figure 3 b) Demonstrates the successful preparation of Finke Co and the poor crystallinity of FFCNS compared with FCNS.
[0054] Catalytic performance test:
[0055] 1) Oxygen evolution reaction (OER) activity test: In an alkaline environment of 1.0 M KOH, the corresponding linear sweep voltammetry (LSV) curves were used to test the activity of FFCNS (Example 1), FCNS (Comparative Example 1), and commercial RuO 2 The oxygen evolution reaction (OER) activities of four catalysts, namely, Ni / Ni and Ni foam (Ni Foam), were evaluated (e.g. Figure 4 ab). The results show that at 10 mA·cm -2 Under the current density of 100 mA·cm, the overpotential of the FFCNS catalyst was only 228 mV, which was significantly lower than that of other comparative samples, showing excellent electrocatalytic activity. -2 When the overpotential is 269 mV, FFCNS can still maintain a low overpotential (269 mV), further demonstrating its excellent catalytic performance at high current density. In addition, the Tafel slope of FFCNS is only 29 mV·dec -1 ( Figure 4 c), indicating that it has excellent kinetic properties. In the stability test of 1000 cycles, we observed that the cyclic stability of the catalyst after the introduction of Finke Co was significantly improved compared with other comparison samples ( Figure 4 d). Compared with FeCoNi / S catalyst, Finke Co-FeCoNi / S has faster charge transfer rate, higher electrocatalytic active surface area and stable electrochemical durability.
[0056] 2) Hydrogen evolution reaction (HER) activity test: at 10 mA·cm -2 At the current density, the overpotential of the catalyst FFCNS (Example 1) is only 75 mV, which is better than the commercial Pt / C (20%) and FCNS (Comparative Example 1) catalysts ( Figure 4 e), and the FFCNS catalyst still maintained excellent activity after 1000 cycles, with little change in overpotential.
[0057] 3) Full water splitting performance test: Since the catalyst FFCNS (Example 1) has dual-functional catalytic activity, a full water splitting device was further assembled, using the catalyst FFCNS at both the cathode and the anode, and compared with the commercial catalyst and the catalyst FCNS (Comparative Example 1). Among them, the Finke Co-FeCoNi / S || Finke Co-FeCoNi / S (cathode, anode) combination was tested at 10 mA cm -2 and 100 mA·cm -2 The overpotential of the device is lower than that of the commercial catalyst combination (Pt / C / NiF|| RuO 2 / NiF) and the FeCoNi / S || FeCoNi / S comparison group, showing excellent overall water splitting performance ( Figure 4 f). And Finke Co-FeCoNi / S || Finke Co-FeCoNi / S at a current density of 10 mA·cm -2 When the battery fully decomposes water, the voltage is 1.52 V, and the cathode of the electrolytic cell releases H 2 , the anode releases O 2 , indicating that the catalyst has excellent performance as a complete water splitting electrode.
[0058] The comparison voltages in all the above tests were based on the reversible hydrogen electrode (RHE).
[0059] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.
Claims
1. A method for preparing a self-assembled low-crystalline nano-flower-shaped polyoxometalate catalyst, characterized in that: The following steps are involved: S1. Dissolve cobalt nitrate hexahydrate in deionized water and add Na8[HPW9O 34 ] After heating until the solution is homogeneous, a precipitate is generated, which is filtered, dried, and then dissolved in water for recrystallization to obtain a sandwich-type polyoxometalate Finke Co; S2, dissolving cobalt nitrate hexahydrate in a mixed solution of deionized water and ethanol, and adding ferric nitrate nonahydrate, urea and the sandwich polyoxometalate Finke Co of step S1 to mix well to prepare a precursor solution; first immersing nickel foam in the precursor solution for hydrothermal reaction, then taking out the nickel foam and immersing it in a methanol solution dispersed with ZIF-67 (Co) for reaction, and finally washing and drying to obtain a nickel foam of Finke-type Co-Fe MOF with uniform growth; S3, dissolving sodium sulfide nonahydrate in deionized water, and adding the nickel foam of Finke-type Co-Fe MOF in step S2 to carry out a sulfidation reaction, washing and drying after the reaction, and finally obtaining the sulfided nickel foam of Finke-type Co-Fe MOF, which is a nanoflower-shaped polyoxometalate catalyst.
2. The method for preparing the self-assembled low-crystalline nano-flower-shaped polyoxometalate catalyst according to claim 1, characterized in that: In step S1, Na8[HPW9O 34 ] was prepared by the following method: Dissolve Na2WO4 in water, add H3PO4 and glacial acetic acid, stir and react, and filter to obtain a white crystal precipitate, which is Na8[HPW9O 34 ].
3. The method for preparing the self-assembled low-crystalline nano-flower-shaped polyoxometalate catalyst according to claim 1, characterized in that: In step S2, when preparing the precursor solution, the molar ratio of cobalt nitrate hexahydrate to ferric nitrate nonahydrate is 0.5:
1.
4. The method for preparing the self-assembled low-crystalline nano-flower-shaped polyoxometalate catalyst according to claim 1, characterized in that: In step S2, the hydrothermal reaction temperature is 100-120 °C.
5. The method for preparing the self-assembled low-crystalline nano-flower-shaped polyoxometalate catalyst according to claim 1, characterized in that: In step S2, cobalt nitrate hexahydrate and 2-methylimidazole are dissolved in methanol to react to obtain ZIF-67 (Co).
6. The method for preparing the self-assembled low-crystalline nano-flower-shaped polyoxometalate catalyst according to claim 1, characterized in that: In step S3, the molar ratio of sodium sulfide nonahydrate to the nickel foam of the Finke-type Co-Fe MOF of step S2 is 2:
1.
7. The method for preparing the self-assembled low-crystalline nano-flower-shaped polyoxometalate catalyst according to claim 1, characterized in that: In step S3, the reaction temperature is 100-120 °C.
8. A polyoxometalate catalyst, characterized in that: The method is prepared by any one of claims 1 to 7.
9. Use of the polyoxometalate catalyst according to claim 8 in OER / HER reactions.
10. Use of the polyoxometalate catalyst according to claim 8 in the complete hydrolysis of water.
Citation Information
Patent Citations
Preparation method of atomic-scale nitrogen-doped molybdenum carbide / vanadium oxide heterojunction electrocatalyst integrally formed through polyacid derivation
CN117488344A
High-activity alkaline electrolytic water oxygen evolution reaction catalyst based on transition metal as well as preparation method and application of high-activity alkaline electrolytic water oxygen evolution reaction catalyst
CN118773654A
Method for preparing tricobalt tetraoxide nanosheet by means of double-confinement of MOF-co and biotemplate
WO2021017049A1
Cited By
Preparation and application of Anderson type polyacid modified Co-MOF nano flower-shaped electrocatalyst
CN119877028A
Preparation and application of anderson type polyacid modified co-mof nanoflower-like electrocatalyst
CN119877028B
Heterojunction composite catalyst of sulfur-doped keggin type molybdenum polyacid and nickel sulfide as well as preparation method and application of heterojunction composite catalyst
CN120844145A
Carbon-nitrogen-doped polyoxometallate catalyst and preparation method and application thereof
CN121272467A
Carbon and nitrogen doped polyoxometalate catalyst, and preparation method and application thereof
CN121272467B